Direct growth of monolayer MoS2on nanostructured silicon waveguides - Kuppadakkath, Athira; Najafidehaghani, Emad; Gan, Ziyang; Tuniz, Alessandro; Gia Quyet Ngo; Knopf, Heiko; Loechner, Franz J. F.; Abtahi, Fatemeh; Bucher, Tobias; Shradha, Sai; Kaesebier, Thomas; Palomba, Stefano; et al. (Nanophotonics, 2022)
We report for the first time the direct growth of molybdenum disulfide (MoS2) monolayers on nanostructured silicon-on-insulator waveguides. Our results indicate the possibility of utilizing the Chemical Vapour Deposition (CVD) on nanostructured photonic devices in a scalable process. Direct growth of 2D material on nanostructures rectifies many drawbacks of the transfer-based approaches. We show that the van der Waals material grow conformally across the curves, edges, and the silicon-SiO2 interface of the waveguide structure. Here, the waveguide structure used as a growth substrate is complex not just in terms of its geometry but also due to the two materials (Si and SiO2) involved. A transfer-free method like this yields a novel approach for functionalizing nanostructured, integrated optical architectures with an optically active direct semiconductor.
CRIS-Team Scopus Importer:2023-04-20
Keywords: 2D materials; excitonic photoluminescence; integrated photonics; transition metal dichalcogenides